Assessment on suitability of raw and composted grinding sludge for agriculture land application - Ahmad Borhanuddin, Izzah Afifah (2015)
This project was conducted to determine the suitability of raw and composted grinding sludge for land application. Grinding sludge is a waste product from the steel and bearing industries. SKF Bearing Industries (M) Sdn. Bhd produced about 480 tons per year of grinding sludge. The grinding sludge is disposed off landfill of Kualiti Alam Sdn. Bhd but the disposal cost is high. In order to utilize the waste, this experiment is conducted to investigate whether it is suitable for land application. However, raw grinding sludge may not be ideal by itself for land application. High concentration of Fe, Cr and Ni content in it may cause toxicity to human health. Therefore, composting the sludge with sawdust might help alleviate the metal toxicity problem. This study is conducted in Ladang 15’s Glass house unit, Faculty of Agriculture, UPM. The experimental design for this study is Split Plot. For each set, there are 5 treatments (0, 2.5, 5, 10, 20 tons/ha) with 4 replications for SET A (raw grinding sludge), and there are also 5 treatments (0, 3.125, 6.25, 12.5, 25 tons/ha) with 4 replications for SET B (composted grinding sludge). The plant material used in this project is sweet maize variety (Zea mays) of Thai Super Sweet. The data collection for soil parameters were soil pH by using pH meter, soil organic matter, soil CEC, and soil EC. Determination of extractable Ni is by the DTPA Method. Determination of extractable Cr is by EDTA Method and determination of extractable Fe is by Dilute Double Acid Method, and total element content of Ni, Cr, and Fe were determined by the Aqua Regia Method. The plant tissues analysis is carried out to determine the total element content of Ni, Cr and Fe using Dry-Ashing Method. The significant difference between the treatments is analyzed using ANOVA test. Correlation analysis between soil parameter and plant analysis is conducted to see any correlation. From this study, it can be concluded that composted sludge is more suitable on land application compared to raw sludge. Correlation study shows that there were some negative correlations. Soil pH and soil total C are negatively correlated with plant Ni concentrations. Based on overall results, the optimum rate of composted grinding sludge for land application is 3.125 t/ha. The highest yield was at this rate. There was no heavy metals toxicity problem with the application of composted sludge at this rate. The plant tissues analysis shows that Ni, Cr and Fe concentrations were still below the toxicity levels. However, the composted sludge that was applied at 3.125 t/ha gives almost the same result as the control. Since at rate 3.125 t/ha composted sludge gives the same results as the control, we can choose not to apply this sludge at. However, to reduce the disposal of this grinding sludge at the land fill, the raw grinding sludge must be composted before applying on land and only suitable to be applied at the rate of 3.125 t/ha.